Married Couples’ Understandings of Family Planning and their Communication Processes - Chitavi, Salome Omuyoma (My University, 2006)
This dissertation examines husbands and wives’ understandings of family planning and communication processes. It examines family planning approval, knowledge of contraceptives and motivations for contraceptive use by husbands and wives. The study provides insights into these variables as held by husbands and wives and implications for contraceptive use. The dissertation also provides insights into the nature of communication processes while relating this to couples’ inconsistencies noted from quantitative data, their marital and reproductive history, and contraceptive use implications. The study uses KDHS 1998 survey Western Province couples’ data set that includes 176 married couples. The study further uses data from Focus Group Discussions conducted amongst husbands and wives in Vihiga District of Western Kenya. The study notes that variables such as contraceptive knowledge, approval of family planning and spousal family planning communication continue to have inconsistent and unclear relationship with contraceptive use. The study argues that these variables are not simply related to contraceptive use and need further examination using qualitative methodologies. The culture and political-economy of fertility conceptual framework and its various aspects of levels, process, causality, time and methodology is applied in the examination of husbands and wives’ understandings of family planning and contraceptive use communication between spouses. The findings of this study reveal that family planning understandings by husbands and wives including knowledge, attitudes and motivations for contraceptive use and spousal family planning communication are related to contraceptive use yet the relationship remains complex and can be understood through examining how different contextual levels and processes enhance varied notions of these factors as held by husbands and wives in relation to contraceptive use; the timing in terms of couples’ marital and reproductive history; the various socio-cultural and politicaleconomic processes surrounding the couples and the individual agency of the husband and wife in pursuing their fertility goals. While none of these factors adequately predicts contraceptive use on their own, an examination of husbands and wives within such a framework provides a better linkage to potential for contraceptive use or lack of it at married couple level. Thus while knowledge or approval of family planning perse fails to provide a clear or consistent link to contraceptive use, the study highlights the various notions of knowledge including individual husbands’ and wives’ perceptions about own knowledge of family planning; and differences in approval ranging from widespread general approval in line with community perceptions, twin perceptions of approval and disapproval common at individual level and disapproval of family planning and the fact that these may change across reproductive histories are factors within the concepts of family planning knowledge and approval that provide better understanding for potential for contraceptive use. The study therefore provides further insights regarding how husbands and wives understand variables commonly related to family planning and varied implications for contraceptive use. With regards to communication, the study underlines that spousal family planning communication is not simply linked to contraceptive use. Instead spousal family planning communication is a complex process informed partly by husbands’ and wives’ understandings of family planning; their perceptions of own knowledge regarding contraceptive methods; their various motivations for family planning involvement and their gender based relationship and perceptions of dominance. The study highlights various forms of spousal family planning communication processes and implications for contraceptive use. This study further argues that the potential of spousal family planning communication’ complex relationship with contraceptive use is related to the nature, timing, content of the communication processes and the agency of the individual husband and wife in influencing spousal family planning communication and decision making. The thesis ends with conclusions and provides recommendations for family planning programs and future studies while highlighting limitations of this study.
Faculty of Arts 9803428v
Keywords: family; communication; timing; husbands